Suppression of Covid-19 outbreak among healthcare workers at the Treviso Regional Hospital, Italy and lessons for ophthalmologists. Issue 6 (November 2021) - Grosso, Andrea; Rigoli, Roberto; Formentini, Stefano; Di Perri, Giovanni; Scotton, Piergiorgio; Dapavo, Giancarlo; Fioretto, Mauro; Scarpa, Giuseppe
Purpose: To describe a strategy to reduce Covid-19 spread among healthcare workers and provide ophthalmologists with recommendations useful for a possible second wave of Covid-19 in Autumn. Methods: Epidemiological surveillance at the Cà Foncello Hospital (Veneto, Italy) since 24 February 2020 to 24 April 2020 when the municipality of Treviso was hit by the Covid-19 outbreak. The number of naso-pharigeal (NP) swabs performed was 7010. Results: The number of infected among healthcare workers was 209/ 3924 (5.32%): medical doctors: 28 cases / 498 (5.6%). None among ophthalmologists; specialized nurses: 86/1294 (6.4%) None in the ophthalmic unit; intermediate care technicians: 68/463 (14.7%). The 46% of the positive tested were asymptomatic. We share key suggested actions for the reorganization in ophthalmological services: be part of a global epidemiological local strategy of containment (Testing, Tracing, Treating); protect your department: Keep on screening patients by telephone interview before entering the hospital; promote continuous and appropriate use of PPE both for doctors and for patients; make any effort to obtain a continuous flow of patients in every line of the ophthalmic service; treat appropriately any single patient with vision threatening condition; avoid unnecessary or futile testings and examinations. Conclusion: The Treviso model shows that it is possible and safe to keep on performing high risk hospital activities like ophthalmology, even in the epicenter of covid outbreak, if adequate actions are performed. We discuss about the value of NP swabs and serological tests as a strategy in case of a second wave of infections.